Nghiên cứu mối quan hệ giữa hoạt tính sinh học của thủy tinh 46S với độ cứng và độ bền nén - Vương, Bùi Xuân (Vietnam Journal of Chemistry, 2017)
A bioactive glass with composition 46SiO2 - 24CaO - 24Na2O - 6P2O5 (wt%) (noted 46S) was elaborated by the melting method. ‘‘In vitro’’ bioactivity of this glass was evaluated by soaking of glass samples in a simulated body fluid (SBF). XRD and SEM analyses showed the bioactivity of this glass by the formation of a bioactive hydroxyapatite (HA) layer on its surface [4, 5]. This paper focuses on the behavior between the glass bioactivity with hardness and compressive strength. Obtained results from experiment show that the hardness of glass fell quickly when the glass was soaked in SBF solution. After 30 days of immersion, the hardness value is similar to natural tooth bone. In contrast, the compressive strength of glass increased. s Keywords. Bioactive glass, bioactivity, hydroxyapatite, ‘‘in vitro’’, hardness, compressive strength.